2012
DOI: 10.1177/1759720x12455959
|View full text |Cite
|
Sign up to set email alerts
|

Significance of C-reactive protein in osteoarthritis and total knee arthroplasty outcomes

Abstract: The results of this study provide support for inflammatory mechanisms contributing to the OA progression, with hs-CRP being a possible predictive variable, combined with BMI and other comorbidities, of post-TKA function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
31
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 24 publications
5
31
0
Order By: Relevance
“…Those with positive CRP results had greater chance to acquire knee OA in contrast to negative CRP findings which had a protective effect. This is in accordance with the three studies done in USA [20][21][22] where they found a correlation between patients with elevated CRP and the presence of inflammatory changes in patients with KOA. They illustrated that the elevated CRP levels seen in these patients might reflect local inflammation within the joint and Interleukin 6(IL-6) is known to be the chief regulator of CRP production and may have a role in the inflammatory OA process.…”
Section: Methodssupporting
confidence: 92%
“…Those with positive CRP results had greater chance to acquire knee OA in contrast to negative CRP findings which had a protective effect. This is in accordance with the three studies done in USA [20][21][22] where they found a correlation between patients with elevated CRP and the presence of inflammatory changes in patients with KOA. They illustrated that the elevated CRP levels seen in these patients might reflect local inflammation within the joint and Interleukin 6(IL-6) is known to be the chief regulator of CRP production and may have a role in the inflammatory OA process.…”
Section: Methodssupporting
confidence: 92%
“…Previous studies showed that the elevation of serum CRP is associated with knee as well as hip osteoarthritis prediction and severity if compared to healthy individuals [29], [30]. Our results demonstrated significant decrease in CRP in US group compared to Lev group and LLLT group.…”
Section: Effects Of Ultrasound Versus Low Level Laser Therapy In Levosupporting
confidence: 60%
“…Elevated high sensitivity C reactive protein (hs-CRP) predicts cartilage loss associated with osteoarthritis, as well as poorer outcomes after total knee joint replacement 57 66 67. Similar effects have also been found for interleukin 6 (IL-6) 57 68.…”
Section: Potential Value Of Biomarkers In Osteoarthritismentioning
confidence: 78%